The Transforming Power of the Gospel. - Bridges, Jerry (NavPress Publishing Group, 2014)
The apostle Paul writes that we are to be transformed, but for many Christians, figuring out how to approach spiritual transformation can be elusive. Bestselling author Jerry Bridges helps us understand that we have available to us the ultimate power source for true spiritual growth: the gospel. In The Transforming Power of the Gospel, Bridges guides you through a thorough examination of: what the biblical meaning of grace is and how it applies to your life how Jesus' work in His life and death applies to the believer in justification and adoption why basic spiritual disciplines are necessary f.